The Impact of Transformational Leadership and Creative Organizational Climate on Employees’ Creativity - Kijački, Dragana (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The most valuable sources of companies’ competitive advantage nowadays aren’t modern technologies or the financial ???ength of the company, but the creative potential of their employees.Companies that grow creativity (creative thinking and behaving), respect and test ideas and suggestions of their employees have the biggest chances to make progress.The current coronavirus pandemic confirmed this.In the new circumstances last year, survival but also progress was ensured by the companies whose employees adapted promptly to the new ways of working, designed crisis plans and ???ategies, and managed to remain committed and focused on achieving goals.Many researchers said that the main role in encouraging employee’s creativity has transformational leadership.It motivates employees to make an additional effort and find new, inventive work and problem-solving approaches.The subject of the research is reflected in the analysis of the importance which transformational leadership has for the employee’s creativity.The paper aims to determine whether or not there is a positive relationship between transformational leadership, its dimensions, and employee’s creativity.Under the influence of transformational leadership comes to the establishing of the creative organizational climate, which components ???ongly motivate employee’s creative thinking in order to increase the performance of the organization. Therefore, this research’s purpose is also to investigate the existence of the positive impact of creative organizational climate on employee’s creativity. The research hypotheses were empirically tested based on a survey that was conducted in the territory of the Republic of Serbia.The survey was developed by combining Multifactor Leadership Questionnaire-MLQ, Creative Climate Questionnaire- CCQ formulated by G.Ekvall, and a creativity survey formulated by Tierney,Farmer and Graen.